Current treatment options for hyperprolactinemia. (August 2013) - Faje, Alexander; Nachtigall, Lisa
<x xml:space="preserve">Abstract</x> Introduction: Hyperprolactinemia is a prevalent cause of oligo-amenorrhea, and prolactinomas are the most common type of functional pituitary tumor. Untreated hyperprolactinemia can lead to bone loss and impair gonadal function and fertility. Normalization of prolactin improves bone mass and restores gonadal function in a majority of patients. Areas covered: This article contains an overview of hyperprolactinemia with an emphasis on pharmacologic, surgical and radiation treatment options. Discussion focuses on the efficacy and safety of available treatments and comments on new and emerging therapies. Expert opinion: Dopamine agonists, usually cabergoline, remain the primary choice for initial treatment of hyperprolactinemia. Surgery may also be an appropriate alternative in certain circumstances. Monotherapy with dopamine agonists is often successful at controlling prolactin levels and tumor size, but adjunctive treatments may be necessary for resistant or aggressive prolactinomas.